Effects of Varying Storage Conditions on the Longevity of Seeds of Ekebergia Capensis - Limo , Reuben K.; Too , Emily J.; Omari , Amuka; Meso , Michael (African Journal of Education,Science and Technology (AJEST), 2021)
Ekebergia capensis is an indigenous tree valued for its medicinal uses. However, it is facing extinction due to excessive utilization without counter efforts to restore them, and its slow regeneration rate in nature. Generation of this tree is mainly through seedlings from physiologically mature seeds. There is limited information on post-harvest storage of seeds of Ekebergia capensis. This study was carried in order to find out the optimum storage conditions and duration of storage of E. capensis seeds that enhance long shelf-life. This study investigated the effects of different moisture contents (MC) and storage temperature regimes on seed longevity of E. capensis seeds for a period 90 days. The seeds were desiccated to three moisture contents (MC) (15%, 25% and 35%) and three storage temperature regimes (-5 o C, 10 o C and 25 o C) for a period of 30, 60 and 90 days. The seeds in storage were retrieved at an interval of 30 days for seed longevity tests. Data analysis was carried using GLM statistical Model (GenSTAT.16) version. Findings from this study showed that E. capensis seeds having higher moisture content of 35% stored in all the three temperature regimes viz: -5 o C, 10 o C and 25 o C maintained significantly higher shelf life compared to other seeds with lower moisture content (25% and 15%) stored across all the temperature regimes. Furthermore, seeds with 35% MC stored at 10 o C retained viability and vigour for the longest period of time as storage period progressed to 90 days. A positive correlation existed between seed longevity and MC. Seed shelf life decreased in the order of 35%>25%>15% MC. This study recommends that seeds of E. capensis can be dried to a moisture content of 35 % and stored at 10 o C for 30 days without any significant loss of the seed germination qualities.